Ketidaklangsungan Ekspresi dalam Antologi Puisi “Ayat-Ayat Api” Karya Sapardi Djoko Damono: Kajian Semiotika M. Riffaterre - Nur Rahma; Mahmudah Mahmudah; Suarni Syam Saguni (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. The source of data in this research is poetry from the poetry anthology "Ayat-ayat Api" by Sapardi Djoko Damono which focuses on "Line, Net, Cold Air, He Never and at the Door". The author focuses on the work of Sapardi Djoko Damono because of the background of his works which are close to god and death which are framed by other signs, as well as his works that are popular and many people recognize him. The five poems in the poetry anthology “Ayat-ayat Api” by Sapardi Djoko Damono include: Lines, Nets, Cold Air, He Never and At The Door. These poems are used as research material in this study. The five poems were chosen as research material because there are many hidden signs, there are diction games that raise a lot of questions. This is very helpful for the author in analyzing because it is the main focus of the author who examines the indirectness of expressions based on M. Riffaterre's semiotic theory. The method used is descriptive qualitative by collecting references related to theory to analyze the poem.  Keywords: Poetry, Riffaterre, sign